Bandgap widening through doping for improving the photocatalytic oxidation ability of narrow-bandgap semiconductors. Issue 1 (7th December 2022) - Yang, Yue; Toyoda, Masayuki; Yamaguchi, Akira; Cho, Yohei; El Aisnada, An Niza; Abe, Hideki; Ueda, Shigenori; Okunaka, Sayuri; Saito, Susumu; Liu, Min; Tokudome, Hiromasa; Miyauchi, Masahiro
Abstract : We introduced an orbital dilution strategy for bandgap widening through doping. Specifically, we found that the lanthanum-doped (La-BiVO4 ) photocatalyst has a wider bandgap and exhibits stronger oxidation power than the pristine BiVO4 . Abstract : The trade-off relationship between narrowing the bandgap and achieving sufficient redox potentials accounts for the hindrance to the development of an efficient photocatalyst. Most of the previous researchers attempt to narrow the bandgap of semiconductors by impurity doping to achieve visible-light sensitivity, but this approach causes the losses of their oxidation and/or reduction ability. Conversely, this study presents a bandgap widening strategy by doping to improve the redox potential of photogenerated carriers. Employing first-principles simulations, we propose the lanthanum-doped bismuth vanadate (La-BiVO4 ) photocatalyst as a wider-bandgap semiconductor exhibiting stronger oxidation ability compared to pristine BiVO4, and the results revealed that the bismuth orbital in the valence band (VB) was diluted by lanthanum-ion doping, while the VB shifted to a higher potential (positively shifted). Thereafter, a La-BiVO4 powder was synthesized via a solid-state reaction, after which its activity was evaluated in the photocatalytic oxidation of 2-propanol (IPA). La-BiVO4 exhibited bandgap widening; thus, the number of absorbed photons under visible-light irradiation was lower than that of pristine BiVO4 . However, the quantum efficiency (QE) of La-BiVO4 for the oxidation of IPA was higher than that of the pristine BiVO4 . Consequently, the photocatalytic reaction rate of La-BiVO4 was superior to that of pristine BiVO4 under the same visible-light irradiation conditions. Although the bandgap of La-BiVO4 is widened, it is still sensitive to the cyan-light region, which is the strongest in the sunlight spectrum. These results demonstrate that the orbital dilution strategy by impurity elemental doping is effective for bandgap widening and contributes to improving the oxidation and/or reduction ability of the photogenerated charge carriers. This study elucidates the possibility of boosting photocatalytic performances via bandgap widening.